Stress Tolerance Assay at the Seed Germination Stage for Tobacco - Ajit Ghosh; Ashwani Pareek; Sneh Singla-Pareek (Bio-Protocol, 2015)
Stress tolerance of plants is a complex phenomenon that depends on the inter-related action of several morphological, physiological and biochemical parameters. Although stress affects normal physiological growth of a plant irrespective of its developmental stage, seed germination and seed setting are considered to be the most sensitive two. Therefore, to evaluate the stress tolerance potential of a particular plant species or variety, rate of seed germination in presence of stress is an important agronomic trait. This will provide a clear indication about the stress tolerance potential with minimum instrumentation facilities. The method is very simple, effective and highly reproducible that would provide quick and reliable results to the researchers.